Leukoplakia Removal by Carbon Dioxide Laser (CO2) Laser - Chiniforush, Nasim; Kamali, Abbas; Shahabi, Sima; Bassir, Seyyed Hossein (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: definitive treatment of oral leukoplakia is very important because of its recurrences and malignant transformation depending on the location, clinical feature,degree of dysplasia and etiological factors. there are different kinds of treatment for this lesion, but using high power laser has some advantages like less pain, swelling, prevention of metastasis, edema, less bleeding (dry surgery) and infection. CASE: a 53_year_old man with leukoplakia lesion with moderate dysplasia on the left side of the ventral surface of the tongue was selected for treatment with co2 laser.the average power is set on 6.2 w with frequency of 20 hz. the irradiation mode was non-contact. the entire lesion evaporated by the laser with a 2 mm safety margin. RESULT: in this case, 80% of lesion had disappeared after 5 weeks and the 20% residual was evaporated again with the same parameters than the first time. no significant clinical differences were seen between the normal and laser-treated tissue. CONCLUSION: using laser in the treatment of oral lesions has many advantages like selective removal of the affected tissues and minimal damage to surrounding tissue, leading to excellent wound healing with no or minimal scar and good functional results.